THE CONTRIBUTION OF THE TOPAT WAR RITUAL IN BUILDING RELIGIOUS MODERATION IN LINGSAR WEST LOMBOK - Made Sumari (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Many local traditions in Indonesia imply collaboration between different groups. In the midst of a multicultural nation's life, collaborative practices between groups can be used as a force in efforts to build harmony and national integrity. The presence of radical groups in several regions of Indonesia can be used as a counterweight. The current value of moderation being put forward fits this practice perfectly. For example, the topat war, a joint ritual between Hindus and Muslims in Lombok, is a unique Indonesian tradition that can be used as a reference for the practice of moderation. They carry out activities together so that communication and collaboration occur in them. Even though their religion is different, the enthusiasm for doing the activity is very high. Here, the differences do not make them lose communication and instead the togetherness within them is able to build values of tolerance, respect and harmony with a life of moderation. Although in essence, this activity is aimed at fertility, as is their agrarian tradition, it contains a noble value that is full of a sense of acceptance of different beliefs..